Pengaruh Literasi Ekonomi dan Peer Influence Terhadap Pembelian Impulsif dengan FOMO Sebagai Mediasi - Aniqotul Athiyah; Mohamad Arief Rafsanjani (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2026)
Technological advancements have driven changes in consumer behavior. One such development is the transformation of social media into social commerce, which has become an increasingly popular online shopping concept. This platform enables users to view and automatically add products to their shopping carts, thereby increasing the tendency toward impulsive buying, particularly among university students as primary users of digital media. This study aims to examine the effect of economic literacy and peer influence on impulsive buying, mediated by Fear of Missing Out (FOMO). The study sample consisted of 215 students and was analyzed using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS). The results of this study indicate that economic literacy has a negative and significant effect on impulsive buying and FOMO, while peer influence has a positive and significant effect on impulsive buying and FOMO. Furthermore, FOMO has a positive and significant effect on impulsive buying and mediates the relationship between economic literacy and peer influence on impulsive buying. This study contributes by examining consumer behavior, particularly cognitive and social factors, in explaining impulsive buying while considering FOMO as a mediating variable that has not been comprehensively studied amid the rising trend of digital shopping.